BUSINESS DEVELOPMENT STRATEGY FOR SPECIALTY COFFEE - Vharessa Aknesia; Arief Daryanto; Kirbrandoko Kirbrandoko (Indonesian Journal of Business and Entrepreneurship (IJBE), 2015)
Specialty coffee is a coffee of premium quality that has been made through various stages of post-harvest processing and strictly controlled to produce distinctive taste of origins. PT Sinar Mayang Lestari is one of the companies that currently produce and develop specialty coffee type, Arabica Java Preanger. The objectives of the study are to examine competitive advantages and develop an alternative strategy that need to be done by PT Sinar Mayang Lestari for their business development. The research methods used are value chain analysis and VRIO framework to explore competitive advantage owned by the company. The result shows the company currently has a temporary competitive advantage of the technological resources and reputation. By using SWOT-AHP technique, the alternative strategies that can be done by company are as follows: 1) increasing the production of natural and honey coffee  type; 2) building coffee center in plantation site for sharing knowledge and innovation media to the farmers; 3) improving the competency of human resource in plantation, post harvest, and promoting area; 4) building management system gradually 5) forwarding integration by building roast and ground coffee business; and 6) maximizing the ability of the land and human resources through research and development.Keywords: competitive advantage, specialty coffee, SWOT-AHP, value chain, VRIOABSTRAKKopi special merupakan kopi dengan kualitas premium yang sudah melalui berbagai tahapan pengolahan pascapanen yang diawasi dengan ketat sehingga menghasilkan cita rasa yang khas sesuai dengan daerah asalnya. PT Sinar Mayang Lestari adalah salah satu perusahaan yang saatini memproduksi dan mengembangkan kopi spesial jenis Arabika Java Preanger. Tujuan dari penelitian ini adalah menganalisis keunggulan bersaing yang dimiliki dan mengembangkan alternative strategi yang perlu dilakukanoleh PT Sinar Mayang Lestari untuk pengembangan usahanya. Penelitian ini menggunakan analisis rantai nilai dan kerangka VRIO untuk mengidentifikasi keunggulan bersaing yang dimiliki perusahaan. Di samping itu, menggunakan analisis SWOT-AHP untuk menentukan alternatif strategi. Hasilnya menunjukkan bahwa perusahaan saat ini memiliki keunggulan bersaing sementara terhadap sumber daya teknologi dan reputasi. Alternatif  strategi yang diperoleh menunjukkan perusahaan kedepannya dapat melakukan langkah-langkah sebagai berikut: 1) memperbanyak produksi kopi jenis natural dan honey; 2) membangun coffee center di lokasi perkebunan untuk sharing knowledge daninovasi kepada petani; 3)meningkatkan kompetensi SDM di bidang perkebunan, pascapanen, dan promosi; 4)membangun sistem manajemen secara bertahap; 5) integrasike depan dengan membangun usaha kopi roasting danbubuk; dan 6) memaksimalkan kemampuan lahan dan SDM yang dimiliki melalui riset dan pengembangan.Kata kunci: keunggulan bersaing, kopi spesial, rantai nilai, SWOT-AHP, VRIO